Hak Mewaris Anak yang Lahir dari Perkawinan Campuran Beda Kewarganegaraan - Devin Irwan Jinoto (Postgraduate University of Merdeka Malang, 2022)
Based on Law Law No. 12/2006 on Citizenship of the Republic of Indonesia has determined the status of children born from mixed marriages of different nationalities is the granting of dual citizenship to the child until the child is 18 years old or before the age of 18 years but has been married and the limit of applying for citizenship elections to choose and follow the citizenship of the mother or the citizenship of the father is for 3 years after the age of 21 years. and for the right to inherit children born from mixed marriages of different nationalities is to use BW (Burgelijk Weetbook) inheritance law, namely children born from mixed marriages of different nationalities will inherit the assets of their parents using the division of inheritance group I (one), which is based on the nuclear family of inheritance division whose heirs only consist of the husband / wife of the heir and the children of their parents / the heirDOI: https://doi.org/10.26905/mlj.v3i1.7930